Metabolism of glycitein (7,4'-dihydroxy-6-methoxy-isoflavone) by human gut microflora - Simons, Andrean L; Renouf, Mathieu; Hendrich, Suzanne; Murphy, Patricia A (Journal of agricultural and food chemistry, 2005)
Gut microbial disappearance and metabolism of the soy isoflavone glycitein, 7,4'-dihydroxy-6-methoxyisoflavone, were investigated by incubating glycitein anaerobically with feces from 12 human subjects. The subjects' ages ranged from 24 to 53 years with a body mass index (BMI) of 20.9-25.8 kg/m(2) (mean BMI = 24.0 +/- 1.1 kg/m(2)). Glycitein disappearance followed an apparent first-order rate loss. Fecal glycitein disappearance rates for the subjects segregated into three different groups described as high (k = 0.67 +/- 0.14/h), moderate (k = 0.34 +/- 0.04/h), and low (k = 0.15 +/- 0.07/h) glycitein degraders (p < 0.0001). There was no dose effect on the disappearance rates for each subject from 10 to 250 microM glycitein (average k = 0.32 +/- 0.03/h, p > 0.05). Four putative glycitein metabolites, characterized by liquid chromatography-mass spectrometry (electrospray ionization using positive ionization mode), were dihydroglycitein, dihydro-6,7,4'-trihydroxyisoflavone, and 5'-O-methyl-O-desmethylangolensin. Two subjects produced a metabolite tentatively identified as 6-O-methyl-equol, and one subject produced daidzein as an additional metabolite of glycitein. These results show that glycitein is metabolized by human gut microorganisms and may follow metabolic pathways similar to other soy isoflavones.